Gender Stereotypes in Students’ English Writing - Atur Semartini (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
Gender stereotypes are guidelines by which a particular gender group behaves as expected based on the existing ideology in the community. Gender stereotypes that are perpetuated by popular culture usually marginalize women, following patriarchal ideology. This popular culture is consumed mostly by the younger generation as well as students. STIKES Nasional is an educational institution where most students are female, and most student organizations are led by female students. This research investigates gender stereotypes in STIKES Nasional students’ writing. This research employs textual analysis focusing on word choice on students’ writing. This study shows that students' writing still represents women as passive and also sensitive or emotional. Women are also still constructed in domestic sphere. Those constructions are implicated in activities carried out by women. On the other hand, men are represented as brave, rational, active, and assertive. Men are also constructed to be in public sphere. Those male constructions are also implicated in men's occupation. Based on the results, it can be concluded that students’ writing affirms the patriarchal gender stereotypes that marginalize women. Patriarchal ideology is still strongly embedded in STIKES Nasional students, though female students dominate in STIKES Nasional.